2017
DOI: 10.1200/jco.2017.35.15_suppl.8573
|View full text |Cite
|
Sign up to set email alerts
|

Pembrolizumab in patients with recurrent thymic carcinoma: Results of a phase II study.

Abstract: 8573 Background: There are few treatment options for thymic carcinoma after chemotherapy. We completed a single institution phase II study of pembrolizumab (P) in patients with recurrent thymic carcinomas. Methods: Main eligibility criteria included: progression after ≥ 1 chemotherapy line, ECOG PS 0-2, no history of autoimmune disease, and adequate organ function. P was given at 200mg IV every 3 weeks. The primary objective of the study was response rate (RR) by RECIST v1.1 criteria; secondary objectives wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…Indeed, clinical trials evaluating the use of these agents in the treatment of thymic carcinoma are already underway and have demonstrated promising preliminary clinical activity. [ 20 ]…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, clinical trials evaluating the use of these agents in the treatment of thymic carcinoma are already underway and have demonstrated promising preliminary clinical activity. [ 20 ]…”
Section: Discussionmentioning
confidence: 99%
“…Currently, two phase II trials examining the efficacy of pembrolizumab in thymic epithelial tumors are ongoing, with response rates of approximately 24%. 4,5 High rates of immune-related adverse events were also reported by Cho et al 5 A phase II trial studying nivolumab in patients with World Health Organization (WHO) type B3 and C thymomas (NIVOTHYM, NCT03134118) is expected to start accrual in 2018.…”
Section: Response To Nivolumab As Salvage Therapy In a Patient With Tmentioning
confidence: 82%
“…3 A twin phase II study testing pembrolizumab in patients with thymic carcinoma showed an ORR of 22.5% and again a high incidence of irAEs (myocarditis, hepatitis, and thyroid disfunctions) probably because of a worsening of autoimmune disorders typically observed in patients with thymic malignancies. 140…”
Section: Thymic Malignanciesmentioning
confidence: 99%